A comparison of serum biochemistry in ankylosing spondylitis, seronegative and seropositive rheumatoid arthritis. Issue 4 (August 1981) - Dixon, J S; Bird, H A; Wright, V
Abstract : The serum biochemistry of 31 patients with ankylosing spondylitis (AS) was compared with that of 80 patients with rheumatoid arthritis (RA) (ARA criteria), 30 of whom were negative for circulating rheumatoid factor and 50 of whom were 'seropositive'. All patients were selected because of moderate to severe disease activity. All 3 groups had distinctive biochemical profiles. Total serum sulphydryl and haemoglobin were particularly good discriminators between AS and RA, IgG, IgA, and acute-phase reactants complemented the sheep cell agglutination test in discriminating between seropositive RA and seronegative RA. In active AS a normal erythrocyte sedimentation rate was often seen in the presence of abnormal C-reactive protein (CRP) and plasma viscosity.